Comparison of Outcomes with Midodrine and Fludrocortisone for Objective Recurrence in Treating Syncope (COMFORTS trial): Rationale and design for a multi-center randomized controlled trial - Arya Aminorroaya (2022)
Background: The cornerstone of the treatment of vasovagal syncope (VVS) is lifestyle modifications; however, some patients incur life-disturbing attacks despite compliance with these treatments which underscores the importance of pharmacological interventions. Methods: In this open-label multi-center randomized controlled trial, we are going to randomize 1375 patients with VVS who had ≥2 syncopal episodes in the last year into three parallel arms with a 2:2:1 ratio to receive midodrine, fludrocortisone, or no medication. All patients will be recommended to drink 2 to 3 liters of fluids per day, consume 10 grams of NaCl per day, and practice counter-pressure maneuvers. In medication arms, patients will start on 5 mg of midodrine TDS or 0.05 mg of fludrocortisone BD. After one week the dosage will be up-titrated to midodrine 30 mg/day and fludrocortisone 0.2 mg/day. Patient tolerance will be the principal guide to dosage adjustments. We will follow-up the patients on 3, 6, 9, and 12 months after randomization. The primary outcome is the time to first syncopal episode. Secondary outcomes include the recurrence rate of VVS, time interval between first and second episodes, changes in quality of life (QoL), and major and minor adverse drug reactions. QoL will be examined by the 36-Item Short Form Survey questionnaire at enrollment and 12 months after randomization. Conclusion: The COMFORTS trial is the first study that aims to make a head-to-head comparison between midodrine and fludrocortisone, against a background of lifestyle modifications for preventing recurrences of VVS and improving QoL in patients with VVS.